Girl Child Empowerment and Socio Economic Welfare in Urban Southwestern Uganda A Case of Kanungu Town Council Kanungu (Global Journal of Human-Social Science, 2018)
The study aimed at establishing the nature of socio-economic welfare of girl-child empowerment interventions in urban Kanungu District through a case of Kanungu Town Council. More specifically, it intended to identify the forms of girl-child empowerment in Kanungu Town Council from 2005 to 2015, to establish the extent to which girl-child empowerment has improved the socio-economic welfare in Kanungu Town Council from 2005 to 2015, to identify and explain the challenges faced by stakeholders in their efforts to empower the girl-child in Kanungu Town Council, and to generate strategies for enhanced girl-child empowerment in Kanungu Town Council. The study adopted a case study research design using a cross-sectional survey. The study population was composed of 15,138 people. Out of the sampled population, the sample size included 332 respondents. Census, systematic random sampling techniques were used to select respondents. Data collection methods included; interviews, questionnaire administration, and documentary review. Data was analysed both qualitatively and quantitatively whereby quantitative data were entered in EPIDATA version 10 and then exported to excel for analysis. The study found out that forms of girl-child empowerment in Kanungu Town Council included; access to education, reproductive health services and income generating.